2012
DOI: 10.1038/npp.2012.124
|View full text |Cite
|
Sign up to set email alerts
|

Histone Regulation in the CNS: Basic Principles of Epigenetic Plasticity

Abstract: Postmitotic neurons are subject to a vast array of environmental influences that require the nuclear integration of intracellular signaling events to promote a wide variety of neuroplastic states associated with synaptic function, circuit formation, and behavioral memory. Over the last decade, much attention has been paid to the roles of transcription and chromatin regulation in guiding fundamental aspects of neuronal function. A great deal of this work has centered on neurodevelopmental and adulthood plastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 179 publications
0
91
0
1
Order By: Relevance
“…Previous structural studies have shown that the bromodomains of BET family proteins form a hydrophobic pocket enveloping acetylated histone tails (Umehara et al 2010a,b). Moreover, histone acetylation is largely, but not exclusively, regarded as a mark for transcriptional activation (Maze et al 2013). Therefore, fs(1)h may be required for transcriptional activation of gene expression, which has been shown in vitro with respect to Ubx (Chang et al 2007).…”
Section: Fs(1)h Is Necessary For Ct Expression and Ct-induced Spike Fmentioning
confidence: 99%
“…Previous structural studies have shown that the bromodomains of BET family proteins form a hydrophobic pocket enveloping acetylated histone tails (Umehara et al 2010a,b). Moreover, histone acetylation is largely, but not exclusively, regarded as a mark for transcriptional activation (Maze et al 2013). Therefore, fs(1)h may be required for transcriptional activation of gene expression, which has been shown in vitro with respect to Ubx (Chang et al 2007).…”
Section: Fs(1)h Is Necessary For Ct Expression and Ct-induced Spike Fmentioning
confidence: 99%
“…The phosphorylation or acetylation of histones is associated with the initiation of gene transcription, whereas the methylation of DNA is generally associated with the repression of gene transcription (Berger, 2007). Importantly, in neuronal cells, extracellular signals can impact epigenetic mechanisms through Ca 2+ signals, the translocation of ERK or other soluble cytosolic proteins to the nucleus (Cohen and Greenberg, 2008;Jordan and Kreutz, 2009;Day and Sweatt, 2011;Maze et al, 2013). Indeed, epigenetic mechanisms are now thought to play a critical role in the formation and consolidation of memory and other cognitive functions (Cohen and Greenberg, 2008;Jordan and Kreutz, 2009;Sweatt, 2010, 2011;Maze et al, 2013).…”
Section: E Cooperation Of Rapid Nongenomic and Genomic Signalingmentioning
confidence: 99%
“…As dopamine receptors and the associated signaling cascade were recently linked to CSCs (58), new insights into the histone methyltransferase G9a suggest a role for such a chromatin writer as a downstream effector of this pathway. Psychoactive drugs are known to have a major impact on neuron epigenetic landscapes and are likely to have similar effects on CSCs (59). Notably, antidepressants, repeated cocaine administration, and dopamine receptor signaling were all linked to G9a deregulation and aberrant H3K9 methylation patterning (60)(61)(62).…”
Section: G9a/glp Histone Lysine Methyltransferase Complexes Affect Wnmentioning
confidence: 99%